Studies in archaeology and ancient cultures in honor of Isaac Gilead - Goldfus, Haim; Gruber, Mayer Irwin; Yonah, Shamir; Fabian, Peter; Gilead, Isaac (Archaeopress, 2019)
'Isaac went out to the field (Genesis 24:63)' presents 28 articles honouring Professor Isaac Gilead on his 71st birthday. Papers on prehistoric and proto-historic archaeology reflect the focus of the honoree's teaching and research, while other subjects including Biblical and Near Eastern studies explore Gilead's other areas of interest.